The The Influence of the number of teachers, total poverty, number of smokers, and regency/city minimum wages on the HDI in East Java Province from 2018 to 2022 - Tanjung, Fahmi; Runtunuwu, Prince Charles Heston (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2024)
The aim of this research is to find out the influence of the quantity of teaching staff, the number of poor people, the number of smokers, and the Regency/City Minimum Wage on the Human Development Index (HDI) for the East Java Region from 2018 to 2022. The data in this research comes from the Central Agency East Java Regional Statistics for 2018 – 2022. The information in this research uses secondary data. The method used in this research is multiple regression. The results of the t test in this review show that the Human Development Index variable in the East Java Region is not influenced by the number of teachers, while the Human Development Index variable is influenced by the amount of poverty, the number of smokers, and the Regional/City Minimum Wage. The F test results in this review show that the factors of the number of educators, the number of poor people, the number of smokers, and the Regional/City Minimum Wage simultaneously influence the Human Development Index.